The Bruton’s Tyrosine Kinase Inhibitor Ibrutinib Impairs the Vascular Development of Zebrafish Larvae - Wang, Kun; Xu, Qiushi; Zhong, Hanbing (Frontiers in Pharmacology, 2021)
Ibrutinib is an orally bioavailable, irreversible selective Bruton’s tyrosine kinase inhibitor that has demonstrated impressive therapeutic effects in patients with B cell malignancies. However, adverse effects, such as bleeding and hypertension, are also reported, implying that studies on the toxicological effect of ibrutinib on living organisms are needed. Here, we have used zebrafish, a successful model organism for studying toxicology, to investigate the influence of ibrutinib during embryogenesis. We found that ibrutinib had potent toxicity on embryonic development, especially vascular development in zebrafish embryos. We also revealed that ibrutinib perturbed vascular formation by suppressing angiogenesis, rather than vasculogenesis. In addition, ibrutinib exposure led to the collapse of the vascular lumen, as well as reduced proliferation and enhanced apoptosis of vascular endothelial cells. Moreover, the expression of vascular development-related genes was also altered in ibrutinib-treated embryos. To our knowledge, this is the first study to describe the vascular toxicity of ibrutinib in an animal model, providing a theoretical basis for clinical safety guidelines in ibrutinib treatment.